(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
The influence of wheat monoculture without the use of mineral fertilizers, the application of 10 t/ha of organic fertilizers with the rise of pure fallow followed by winter wheat throughout the year, sowing its legumes and perennial alfalfa on the dynamics of wheat biomass accumulation was studied.